Nosotros e vosotros: a Guerra das Malvinas 25 anos depois - relatos de ex-combatentes - Bernardi, Caren Luciane (2008)
The main purpose of this study is to examine the reports and memories of veterans of the Malvinas War and understand how they are treated by society and the rule of post-war until today. Question is: To what extent the ex-combatants were welcomed by society argentina in post-war? There are also other questions needed to understand the theme: how they see themselves? How want to be seen? What relationships built with their compatriots from this situation? The veterans interviewed have an average age of 43 years. Three of them were part of the 5 th Marine Battalion of Infantry (BIM 5), living in Buenos Aires, and was a part of the Argentine Army, residing in La Plata. It was used Oral History Subject, as a methodology that aims to understand and deepen knowledge about certain reality - the cultural patterns, social structures and historical processes, obtained through oral reports. Falkland was to balance more than 600 dead and 1200 injured. The conflict began abruptly on April 2, 1982, with the military occupation of the Falkland Islands by Argentine troops, causing the reaction in Britain. Argentina has lived one of the most bloody military dictatorships of Latin America, and President Leopoldo Galtiere was determined to exploit the spontaneous popular support the recovery of the islands in an attempt to awaken in people a sense that nationalist distract the attention of terrors promoted by the state. The hostilities closed on June 16, 1982, with the surrender of Argentina, after 74 days of war. The consequences of post-war were serious, translated into high rates of suicide and psychological disorders. As a result of these events, we have the silence of society on the subject and the purpose of ex-combatants to oblivion, ignoring those who supported the "cause" Malvinas, this question so passionately rooted to the heart of the people of Argentina.